POLA HUBUNGAN BADAN PERMUSYAWARATAN DESA (BPD) DENGAN PEMERINTAH DESA DALAM PEMBANGUNAN DI DESA DANAU LANCANG KECAMATAN TAPUNG HULU KABUPATEN KAMPAR TAHUN 2014-2015 - Endi "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the relationship patterns Village Consultative Body (BPD) with the village government in the construction of the Village of Danau Lancang Village in District of Tapung Hulu Kampar Regency. This study uses qualitative research methods with descriptive research, which can be interpreted as a problem-solving process was investigated by describing the state of the research subjects were based on the facts that appear during the study were then followed by the popularity of existing theories. The presence of the Village Consultative Body with the village government as an arbitrary function and is expected to create a system of check and balances in the manufacture of village development planning. The pattern of parallel relationship between members of the Village Consultative Body and village heads as to which is set in the legislation turned out to be in the implementation, marred by practices working relationships are less harmonious and leads to the occurrence konfik and realize the tendency of domination of the village chief on Village Consultative Body into the Development village, because there is often confusion between the one with the other, it seems the notion of village government who consider BPD is not as opponents but partners, as well as BPD who feel that their presence is not appreciated. The conclusion of this study is BPD Danau Lancang Village can not perform its function well, the lack of coordination between the BPD and the village government in rural development. In addition, the lack of effective communication between BPD and the fabric of society in rural development. To that end, the advice given is the need for coordination and cooperation, in addition to enhanced pattern of relationships intensive communication and coordination with the good. Keywords: Pattern Relations, dominating, collusive, conflictual, Partnership